Circular economy and virtual reality in advanced BIM‐based prefabricated construction - O’Grady, Timothy M.; Brajkovich, Nicholas; Minunno, Roberto; Chong, Heap-Yih (John); Morrison, Greg (MDPI, 2021)
This paper presents a new virtual reality (VR)‐based approach to advanced learnings and experiences of the circular economy (CE) in the construction industry. The approach involves incor-porating game design and a building information modelling (BIM) digital twin of a purposed CE prototype building. Our novel approach introduces VR environments designed to provide a visual representation of materials and components that can be reintroduced into the supply chain at the end of life and their removal procedures and material provenance. A case study methodology was applied to a purposely designed CE building, namely the Legacy Living Lab (L3). To reflect the real-life building, L3’s BIM model was combined with Unify game software to advance the literature in three key areas. First, the research investigates VR tools that will allow building designers to view and implement their strategies to advance CE design. Second, this research proposes an advanced VR tool to visualise the bill of quantities (BoQ) and material stock embedded in the studied building, further understanding concepts such as buildings as material banks. Finally, the proposed VR environment defines CE techniques implemented within the case study to be disseminated across the vast construction industry. This VR research identifies three key pillars in reducing the waste gen-erated by the construction industry: education, documentation and visualisation. Furthermore, this paper provides a visual link between the BIM, BoQ and resiliency of the selected materials.